Sedasi Analgesi Untuk Kardioversi Elektrik Di IGD - Kurniawan Agung Yuwono (The Indonesian Heart Association, 2013)
General practitioner assigned in emergency room must have ability to do electrical cardioversion either in emergency, urgent or elective setting. Analgetic sedation is mandatory to avoid severe pain during electrical cardioversion. Limited number of anesthesiologist and emergency setting that need prompt electrical cardioversion warrant of selecting and using of analgetic sedation agents by doctor in emergency room. Characteristics of those agents must have strong analgesic effect and rapid onset and offset, minimize pain and anxiety and maximize amnesia with minimal adverse effect. This paper reviews some randomized control trial of those agents.